Upaya Pengentasan Kemiskinan Melalui Lembaga Keuangan Syariah Di Provinsi Sumatera Selatan - Raras Risia Yogasnumurti; Muhammad Hafizh; Tsurayya Syarif Zain; Heni Yuvita (LPPM, 2023)
Poverty is a problem in various countries around the world that makes their governments look for solutions to alleviate the ruins. In the Islamic economy there are tools that can deal with the problem of poverty, namely through the distribution of zakat and capital development through Islamic bank and non-bank financial institutions. South Sumatra has 97.17% of the population who adhere to the Muslim religion, it should be able to have a positive impact on alleviating poverty locally and nationally. The biggest thing that caused chaos to increase in South Sumatra was the occurrence of a comprehensive disaster in various countries, namely COVID 19 which changed new conditions where people had to be able to adapt. Distribution of zakat and business development through BMT is one way out to minimize this poverty.